2012
DOI: 10.1007/s00213-011-2634-4
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic classification and gambling in patients with schizophrenia receiving medication: comparison of risperidone, olanzapine, clozapine and typical antipsychotics

Abstract: Results generally supported the hypothesis that patients treated with risperidone perform more like those treated with typical antipsychotics than those treated with other atypical antipsychotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
1
7
1
Order By: Relevance
“…First, the patients were receiving antipsychotic medications at clinicallydetermined dosages, which could have impacted performance on the PRL task. 47,48 However, we did not find any association between PRL task performance and dose or type of antipsychotic medication dose (expressed in oral-chlorpromazine-equivalent units). Further, reversal learning deficits and reduced reward-related striatal activation have been found in unmedicated and first-episode schizophrenia patients.…”
Section: F Reddy Et Alcontrasting
confidence: 37%
“…First, the patients were receiving antipsychotic medications at clinicallydetermined dosages, which could have impacted performance on the PRL task. 47,48 However, we did not find any association between PRL task performance and dose or type of antipsychotic medication dose (expressed in oral-chlorpromazine-equivalent units). Further, reversal learning deficits and reduced reward-related striatal activation have been found in unmedicated and first-episode schizophrenia patients.…”
Section: F Reddy Et Alcontrasting
confidence: 37%
“…Impaired decision-making on the IGT has also been observed in people with binge eating disorder and sufferers of alcoholism (Danner et al, 2012;Le Berre et al, 2014). Similarly, patients with schizophrenia also exhibit deficient IGT performance (Kim et al, 2009;Wasserman et al, 2012;Brambilla et al, 2013;Fond et al, 2013), although this finding has not been consistently observed (Turnbull et al, 2006). The IGT deficits of patients with schizophrenia appeared to be driven by altered learning of reward and punishment contingencies associated with different choices as they did show improved performance over the course of learning but at a slower rate (Kim et al, 2009;Brambilla et al, 2013;Fond et al, 2013).…”
Section: Impaired Decision-making Across Neuropsychiatric Populationsmentioning
confidence: 86%
“…Recent studies suggest that initial deck preferences are driven towards decks with a high probability (0.9) of reward (bad deck B and good deck D) compared to decks with a lower probability (0.5) of reward (bad deck A and good deck C) [2] , [3] , [4] . Thus, advantageous decision-making relies on shifting choice away from bad deck B and replacing choices with good decks C and/or D [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%
“…The major questions addressed were: 1) are deck choices initially driven toward decks with high reward frequency, 2) how do individual deck choices shift as learning occurs, and 3) does intervening sleep between sessions enhance performance? Given previous work, we hypothesized that there would be an initial preference for deck B and D [2] , [3] , [4] and that learning would reflect a decrease in choices from bad deck B and increase in choices from good decks C and/or D [5] , [6] . We expected that those who engaged in post-learning sleep would show greater overall improvement than those in the post-learning wake condition.…”
Section: Introductionmentioning
confidence: 99%